(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the physic-chemical indicators that determine the commodity status characteristic of beer products, gives criteria for differentiating existing product codes and assigning product codes to the new types of products, as well as the features of applying new express analysis methods.